BLENDER AS A 3D CHARACTER DESIGN ALTERNATIVE: DEFINING THE VISUAL STYLE OF VIDEO GAMES - Nebesnyk, Yuriy; Nebesnyk, Ivan (Theory and practice of design, 2025)
Purpose is to explore the potential of using Blender as an alternative to commercial software for creating 3D characters in video games. To identify the advantages and limitations of Blender compared to industry standards. Methodology. The research employs a comprehensive approach that combines the following methods: сomparative analysis – conducted a detailed comparison of Blender with leading commercial software; empirical research – implemented an experimental project to create a 3D character named Alice as fan art based on the game Alice: Madness Returns (2011), aiming to test Blender’s ability to handle all stages of modeling; content analysis – analyzed literary sources, technical documentation, reviews of professional artists, and industry standards, considering current trends in character design across various graphic styles: photorealism, stylized realism, low-poly, and cel shading; case study – examined practical cases of Blender’s use in professional environments, specifically analyzing the workflows of renowned companies like Rocksteady, Ubisoft, and Epic Games. Analysis of experimental data. Evaluated the effectiveness of Blender’s resource optimization methods, such as retopology, Normal and Bump maps, UDIM, and PBR texture maps. Assessed Blender’s performance on computers with limited resources (8 GB RAM) compared to high-performance systems (64-128 GB RAM). Results. Blender has demonstrated its competitiveness in creating 3D characters for video games, particularly in photorealism, stylized realism, low-poly, and cel shading styles. Despite its technical limitations, Blender’s functionality allows achieving professional results without significant financial investment. The study revealed that with proper workflow optimization, Blender can effectively replace costly commercial solutions in small studios, educational institutions, and among independent 3D artists. Scientific novelty. This article offers a systematic approach to analyzing Blender’s potential for creating 3D characters in the video game industry. For the first time, the technical limitations of Blender and ways to overcome them in professional practice have been thoroughly examined. The study proposes approaches to optimizing the process of creating 3D characters using Blender to achieve the required quality in various graphic styles. Practical relevance. The research findings will be valuable for students, independent 3D artists, small studios, and educational institutions seeking accessible tools for creating 3D characters.